Pneumotoraks Bilateral dan Transaminitis Non Spesifik pada Silikosis: [Bilateral Pneumothorax and Transaminitis in Silicosis Patient: A Case Report] - Sahrun Sahrun; Winariani Koesoemoprodjo; Ariani Permatasari (Jurnal Respirasi, 2018)
Background: Silicosis is a fibrosis in the lung caused by inhalation, retention, and reaction to crystalline silica. The prevalence rate is potentially increasing throughout the world. Cases of bilateral spontaneous pneumothorax and transaminitis due to complications of silicosis are very rare. In this case, the patient was presented with bilateral secondary spontaneous pneumothorax as well as in the development of the diagnosis of silicosis, liver dysfunction, and pneumonia. Case: A 36-year-old male was admited to hospital with shortness of breath, the patient was once stone artisans for 7 years, rarely using PPE. Bilateral pneumothorax was established based on the results of clinical and radiological examinations. HRCT showed that it supported silicosis, left fluidopneumothorax, and right pneumothorax. Bronchoscopy was not possible due to the incompatible conditions and subsequently the patient was examined for silica levels from both plueral fluid with significant pleural silica. Summary: Diagnosis of pulmonary silicosis was done by clinical, radiological, and silica analysis of bronchial rinses, but certain conditions of silica could be found from pleural fluid. Silicosis therapy with complications until recently is only symptomatic, definitive therapy has not been found. Silicosis complications can be from pneumothorax bilateral (rarely), tuberculosis, transaminitis, and pneumonia. Conclusion: Pulmonary silicosis can be found from pleural fluid when the amount is large enough, fibrosis and extensive lung damage occurred. Silicosis can have an impact on pneumothorax, liver disorders, pneumonia, tuberculosis, and respiratory problems.